The Effect of Adding Egg Shells to Moist Feed on The Specific Growth and Survival Rate of Lobster Panulirus sp (Torani Journal of Fisheries and Marine Science, 2021)
Sea lobster is a commodity that has high value in both national and international markets. Globally, the demand for sea lobster is increasing by about 15% per year. During growth, lobsters undergo a moulting process. Moulting/ecdysis is a very important process in the life cycle of arthropods (including decapods) because shell release is a must for growth and metamorphosis. In improving and assisting the molting process in lobsters, it is assisted by the provision of additional calcium from egg shells. Egg shells contain 94% calcium carbonate, 1% calcium phosphate, 1% magnesium carbonate and 4% organic compounds. In this study, an experiment was conducted on the addition of feed with a mixture of egg shells to support post-moulting optimization and supplement calcium requirements for lobster larvae. The percentage of egg shells as treatment, namely treatment A (0%), B (5%), C (10%), and D (15%) of the total feed to be made for sea lobster. Maintenance is carried out in a controlled tub, for four months. The highest specific growth obtained in this treatment was treatment A (0.06-0.21%) and the lowest was treatment D (-0.02%)-(-0.37%). Furthermore, the highest survival rate was obtained in treatment A (66.7%) and the lowest in treatment D (33.3%), the highest number of molting lobsters was in treatment A (77.8%) and the lowest was treatment D (33.3%). This shows that the addition of eggshell flour to moist lobster feed has not had a significant effect. For further development, it is necessary to research related to the use of additional ingredients in moist feed for lobster.